The role of internal affairs agencies in ensuring economic security of the regions of Russia - Minakov A. V., Ivanova L. N. (Relevant issues of the Russian Federation law enforcement's activity, 2025)
To ensure stable development of regions, it is important to ensure regional economic security. The central place in this system is occupied by the internal affairs agencies (IAA). The purpose of the study is to study the role of law enforcement agencies in ensuring the economic security of the region. The article uses the following research methods: analysis of theoretical sources, statistical and comparative analysis. The role of the IAA in ensuring the economic security of the Magadan Region is analyzed. At the same time, it is concluded that the increase in the number of identified economic crimes is a negative fact characterizing a decrease in the level of economic security in the region. To improve economic security in the region, it is necessary to develop education and inform the population about the risks and methods of preventing economic crimes. It is also important to strengthen financial liability for such crimes.
Keywords: экономическая безопасность; economic security; regional security; органы внутренних дел; экономические преступления; региональная безопасность; борьба с преступностью; economic crimes; деятельность ОВД; activities of the Internal Affairs Department; internal affairs agencies; combating crime